Consensus Core Point‐of‐care Ultrasound Applications for Pediatric Emergency Medicine Training. Issue 3 (14th March 2019) - Shefrin, Allan Evan; Warkentine, Fred; Constantine, Erika; Toney, Amanda; Uya, Atim; Doniger, Stephanie J.; Sivitz, Adam Brand; Horowitz, Russ; Kessler, David
Abstract: Background: Pediatric emergency medicine (PEM) physicians have variably incorporated point‐of‐care ultrasound (POCUS) into their practice. Prior guidelines describe the scope of POCUS practice for PEM physicians; however, consensus does not yet exist about which applications should be prioritized and taught as fundamental skills for PEM trainees. Members of the PEM POCUS Network (P2Network) conducted a consensus‐building process to determine which applications to incorporate into PEM fellowship training. Methods: A multinational group of experts in PEM POCUS was recruited from the P2Network and greater PEM POCUS community if they met the following criteria: performed over 1, 000 POCUS scans and had at least 3 years of experience teaching POCUS to PEM fellows, were a local academic POCUS leader, or completed a formal PEM POCUS fellowship. Experts rated 60 possible PEM POCUS applications for their importance to include as part of a PEM fellowship curriculum using a modified Delphi consensus‐building technique. Results: In round 1, 66 of 92 (72%) participants responded to an e‐mail survey of which 48 met expert criteria and completed the survey. Consensus was reached to include 18 items in a PEM fellowship curriculum and to exclude two items. The 40 remaining items and seven additional items were considered in round 2. Thirty‐seven of 48 (77%) experts completed round 2 reaching consensus to include three more items and exclude five. The remaining 39 items did not reach consensus for inclusion or exclusion. Conclusion: Experts reached consensus on 21 core POCUS applications to include in PEM fellowship curricula.